Gender Differential Transcriptome in Gastric and Thyroid Cancers - Sousa, Abel; Ferreira, Marta; Oliveira, Carla; Ferreira, Pedro G. (Frontiers in Genetics, 2020)
Cancer has an important and considerable gender differential susceptibility confirmed by several epidemiological studies. Gastric (GC) and thyroid cancer (TC) are examples of malignancies with higher incidence in males and females, respectively. Beyond environmental predisposing factors it is expected that gender-specific gene deregulation contributes to this differential incidence. We performed a detailed characterization of the transcriptomic differences between genders in normal and tumour tissues from stomach and thyroid, using GTEx and TCGA data. We found hundreds of sex-biased genes (SBGs). Most of the SBGs shared by normal and tumour belong to sexual chromosomes, while the normal and tumour-specific tend to be found in the autosomes. Expression of several cancer-associated genes is also found to differ between sexes in both types of tissue. Thousands of differentially expressed genes (DEGs) between paired tumour-normal tissues were identified in GC and TC. For both cancers, in the most susceptible gender the DEGs were mostly under-expressed in the tumour tissue, with an enrichment for tumour-suppressor genes (TSGs). Moreover, we found gene networks preferentially associated to males in GC and to females in TC, and correlated with cancer histological subtypes. Our results shed light on the molecular differences and commonalities between genders and provide novel insights in the differential risk underlying these cancers.